Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Dissolved Oxygen May Limit the Suitability of Salt Marsh as Nekton Habitat - Andrew Clark; William T. Ellis; Alexandra R. Rodriguez; Ronald Baker (Estuaries and Coasts, 2025)
Salt marshes of the northern Gulf of Mexico provide many ecosystem services, including supporting some of the USA’s most productive fisheries. Early work identified links between salt marsh area and commercial shrimp landings, while more recent research highlighted the importance of marsh edge. Many species appear to be restricted to the outer few meters of the vegetated marsh even when large areas are flooded for extended periods. We hypothesized that low dissolved oxygen (DO), driven by high respiration rates, may limit more extensive use of flooded marsh. To evaluate this, we continuously logged DO 5 cm above the substrate along transects at 10, 5, and 1 m into open water adjacent to the marsh edge and at 1, 5, and 10 m into the flooded marsh, for 48+ h periods at 10 sites in Mississippi Sound, AL, during the summer of 2024. DO levels 10 and 5 m into the flooded marsh regularly dropped to stressful levels (< 4 mg/L), often becoming hypoxic (< 2 mg/L) for periods of several hours. In addition to predictable diurnal DO cycles, we identified precipitous drops in DO on the flooded marsh surface around midday at some sites, coinciding with the beginning of the ebb tide. This suggests that even during bright sunny conditions, respiration can exceed aquatic photosynthesis in the shallow flooded marsh. Our findings suggest that much of the flooded marsh may be physiologically stressful for many aquatic species. Increasing temperatures and nutrient loads in our coastal waters will further exacerbate poor DO conditions and may degrade the suitability of this essential fish habitat.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Effects of varying types and amounts of herbivory and nutrient enrichment on a tropicalizing seagrass meadow - Alexandra R. Rodriguez; Candela Marco-Méndez; Justin Campbell; Kenneth L. Heck (Frontiers in Marine Science, 2022)
Climate change is impacting marine ecosystem community dynamics on a global scale. While many have assessed direct effects of climate change, indirect effects on marine ecosystems produced by biotic interactions remain poorly understood. For example, warming-induced range expansions and increased consumption rates of herbivores can lead to significant and unexpected changes in seagrass-dominated ecosystems. To better understand the threats tropicalization presents for the functioning of turtlegrass ( Thalassia testudinum ) meadows, we focused on the extensive turtlegrass beds of St. Joseph Bay, Florida in the northern Gulf of Mexico, a location with increasing numbers of tropically-associated green turtles. Our goals were to investigate experimentally how different grazing rates (natural and simulated),including high levels reflective of green turtle herbivory, coupled with nutrient supply, might alter turtlegrass structure and functioning in a higher latitude, subtropical turtlegrass meadow. We found that 4 months of varying levels of herbivory did not affect turtlegrass productivity, while 7 months of herbivory reduced percent cover, and 10 months reduced shoot density. Nutrient additions had few important effects. Ten months into the study, a massive recruitment of the herbivorous sea urchin ( Lytechinus variegatus ), whose densities reached 19 urchins/m 2 completely overgrazed our study area and a large portion of the lush turtlegrass meadows of St. Joseph Bay. While local turtlegrass overgrazing had been previously noted at these urchin densities, a total loss of seagrass in such a large area has rarely ever been recorded. Overgrazing of the kind we observed, likely a result of both urchin and increasing green turtle grazing, can result in the loss of many key ecosystem services. As tropicalization continues, understanding how changes in biotic interactions, such as increased herbivory, affect higher latitude seagrass meadows will be necessary for their proper management and conservation.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Approaching a Tipping Point? Herbivore Carrying Capacity Estimates in a Rapidly Changing, Seagrass-Dominated Florida Bay - Alexandra R. Rodriguez; Kenneth L. Heck (Estuaries and Coasts, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)